Regional Macro Policies for People's Happiness - Nuraini, Ida; Ananda, Candra Fajri; Muljaningsih, Sri; Wahyudi, Setyo Tri (Universitas Muhammadiyah Ponorogo, 2024)
Currently, the most complete measure of community welfare is the happiness index because this measure is based on community subjectivity. This study aims to determine the effect of per capita income, minimum wage, income inequality and gross enrollment rates on the Happiness Index in Indonesia. The research objects are 34 provinces in Indonesia. The data used are secondary data for 2014, 2017 and 2021. The data source is the Indonesian Central Bureau of Statistics. Using the panel data regression, the results show that per capita income, income inequality, minimum wage and gross enrollment rates together have a significant effect on the happiness index. and partially the per capita income variable has no significant positive effect on the happiness index while income inequality has no significant negative effect on the happiness index, conversely the minimum wage variable and gross enrollment rate have a significant positive effect on the happiness index in Indonesia. In order to increase the happiness index, it is recommended that the provincial government periodically review the minimum wage policy, increase the gross enrollment rate and increase per capita income and reduce income inequality.